THE USE OF E-LEARNING TOOLS IN TRAINING AND THE DEVELOPMENT OF SOCIAL-DIGITAL COMPETENCES IN THE GENERATIONAL Z GROUP - Izabela A. KOŁODZIEJ; Magdalena BOROWSKA (Humanities and Social Sciences)
This paper analyzes the socio-digital competencies developed by Generation Z as a result of using remote tools in education, training, and remote work. The research was conducted with quantitative and qualitative methods, using a proprietary online survey and interviews with students. The survey, created in MS Forms, included closed, semi-open, and multiple-choice questions. One hundred and fifty-one economically active second-year students of Management and Production Engineering at the Wrocław University of Economics in the 2020/2021 summer semester were surveyed. Results indicated that remote learning tools contribute to the development of both social competencies (such as creativity, motivation, emotional intelligence, communication skills, and cognitive curiosity) and digital competencies (e.g., design, use of media and applications, ability to protect information/data, ability to use information/data, and handling AI). As a result, examples of social-digital competencies were proposed, such as proficiency in creative design or the ability to achieve digital comfort. The conscious development of these competencies by the management of modern companies is expected to better respond to the needs of Generation Z.